P–457 Emergency fertility preservation (FP) in female patients- utilisation rate of the stored eggs/embryos and pregnancy outcomes. (6th August 2021) - Balakumar, V; Khaw, S C; Milne, P; Kini, S
Abstract: Study question: The aim of the study was to determine the percentage of patients returning to use their stored eggs/embryos following FP and their pregnancy outcomes. Summary answer: The patient utilisation rate for eggs/embryos was 17% with a live birth rate of 59%. What is known already: Fertility preservation is considered as a vital issue for individuals in the reproductive stage of life when their future fertility may be compromised. Increased cancer survival rate and advances in assisted reproductive techniques make this an essential service to offer to patients facing life limiting disease or long-term medical conditions.FP is important to improve the quality of life in cancer survivors. Study design, size, duration: A retrospective analysis was performed over a period of ten years between January 2010 to December 2020 in our tertiary unit. A total of 75 patients who underwent FP were identified. Participants/materials, setting, methods: Infertility database for embryology and andrology (IDEAS) was used for the data collection and analysis. Patient's age, reasons for fertility preservation, type of benign/cancer condition, protocol used for controlled ovarian stimulation (COS), dose of the gonadotropins, number of eggs collected, number of eggs/embryos cryopreserved, duration between storage and fertility treatment, pregnancy outcomes were included in the analysis. Main results and the role of chance: Seventy-five patients underwent FP during the 10-year study period. The mean age was 30 years (range 17–43). Seventy-two patients (96%) underwent treatment for oncological reasons and the rest (4%) were for gender transition and Crohn's disease. The most common types of malignancies include breast cancer (36%), Hodgkin's lymphoma (18%) and cervical cancer (15%). Ninety-two percentage of patients underwent COS with an antagonist cycle, with an average of 10.8 eggs collected. Recombinant follicle stimulating hormone (FSH) was used in 92% of the cycles and human menopausal gonadotropin (HMG) was used in 8%. Fifty-eight percentage were given a maximum dose of 300IU of gonadotropin. The mean yield of eggs was higher in patients with breast cancer (12.62) followed by Hodgkin's (10.5) and cervical cancer (9.6). Majority (60%) had embryo cryopreservation (82% at blastocyst stage and 18% at day 3 cleavage stage) and the rest (40%) had egg cryopreservation. A total of 17% (12) of patients returned for treatment with a livebirth rate of 59% and miscarriage rate of 8%. One third of livebirths were achieved through surrogacy. The average duration between fertility preservation and return for treatment was 2.4 years. Limitations, reasons for caution: During the last 5 years, there has been an increase in the number of young women requiring FP in our unit. These women may require a considerable amount of time to complete their oncological treatment before embarking on pregnancy using their stored eggs/embryos. Wider implications of the findings: As cancer survival rate improves, there will be a likely increase in the utilisation rate for follow up treatment among young women who had FP. The overall awareness of the gonadotoxic effect of cancer therapy and available fertility preservation options among both patients and clinicians needs to be increased. Trial registration number: NA